Development of potent and effective synthetic SARS-CoV-2 neutralizing nanobodies - Maxwell A. Stefan; Yooli K. Light; Jennifer L. Schwedler; Peter R. McIlroy; Colleen M. Courtney; Edwin A. Saada; Christine E. Thatcher; Ashlee M. Phillips; Feliza A. Bourguet; Catherine M. Mageeney; Summer A. McCloy; Nicole M. Collette; et al. (Taylor & Francis Group, 2021)
The respiratory virus responsible for coronavirus disease 2019 (COVID-19), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected nearly every aspect of life worldwide, claiming the lives of over 3.9 million people globally, at the time of this publication. Neutralizing humanized nanobody (VHH)-based antibodies (VHH-huFc) represent a promising therapeutic intervention strategy to address the current SARS-CoV-2 pandemic and provide a powerful toolkit to address future virus outbreaks. Using a synthetic, high-diversity VHH bacteriophage library, several potent neutralizing VHH-huFc antibodies were identified and evaluated for their capacity to tightly bind to the SARS-CoV-2 receptor-binding domain, to prevent binding of SARS-CoV-2 spike (S) to the cellular receptor angiotensin-converting enzyme 2, and to neutralize viral infection. Preliminary preclinical evaluation of multiple VHH-huFc antibody candidates demonstrate that they are prophylactically and therapeutically effective in vivo against wildtype SARS-CoV-2. The identified and characterized VHH-huFc antibodies described herein represent viable candidates for further preclinical evaluation and another tool to add to our therapeutic arsenal to address the COVID-19 pandemic.